Oficium ke sv. Norbertovi a jeho vývoj - Sojka, Václav (Charles University, 2016)
Keywords: 🛐 liturgy

Geneza i historia Rytu Premonstrateńskiego - Wendland, Mateusz (Liturgia Sacra, 2016)
The Premonstratensian, or Norbertine Rite is strictly related to the Order of Canons Regular, also known as the White Canons. Founded in the 12th century by Saint Norbert, the order at first adhered to liturgical practices that were common among the Canons Regular of Saint Augustine. The following article talks about the genesis and development of Norbertine liturgy, which survived the changes in practices made by the Council of Trent, but was eventually made obsolete by the Second Vatican Council.
Keywords: 🛐 liturgy

Un bréviaire monumental de 1139 destiné aux prémontrés (?) de Knechtsteden (?) (Codex Bruxellensis 104) - Philippart, Guy (Amicorum societas: mélanges offerts à François Dolbeau pour son 65e anniversaire, 2013)
Keywords: knechtsteden; 🛐 liturgy

Le Graduel de Bellelay, aux origines de la liturgie prémontrée - Cullin, Olivier (Le livre et l'écrit. Texte, liturgie et mémoire dans l'Èglise du Moyen Âge, 2012)
Keywords: bellelay; 🛐 liturgy